Native courts system in Sabah: will it continue to survive? / Rafidah@Malissa Salleh - Salleh, Rafidah@Malissa (2014)
Native courts system is a unique feature of Sabah legal system. It serves as a mechanism for settling disputes concerning breach of customary law among the natives in the state. Sabah, which was previously known as North Borneo, was a British protectorate from 1881 until 1946. The British North Borneo Company at that time recognized native customary law and rendered formal recognition to it, as stated in Article 9 of the Royal Charter. Prior to Sabah gaining its independence from British, administration of the native law was based on the native courts presided by native chiefs, elders and the village headmen. The court received its first official title in Village Administration, Proclamation V of 1913. When Sabah joined Sarawak and Malaya to form Malaysia in 1963, the courts system continues to become an integral part of the state legal system. And pursuant to the Federal Constitution of Malaysia, native courts, and the enforcement of native customary law are considered as state matters to be regulated by state legislation. Now, the courts system is governed by Sabah Native Courts Enactment 1992. It is contended that native courts system is an important part of the judicial system in Sabah as 75 per cent of natives bring their matters to native courts, instead of the common courts. Thus, this paper will examine the native courts system, discuss some of the emerging issues in the system, and finally provides the answer as to whether the native courts system will continue to survive in the modern world.